ANALISA HUKUM DALAM MENERAPKAN PERATURAN PENGADAAN TANAH UNTUK KEPENTINGAN UMUM ANTARA BADAN PERTANAHAN REPUBLIK INDONESIA DENGAN KEJAKSAAN REPUBLIK INDONESIA (Studi di Kota Singkawang) - MUHAMMAD WALID, S.SIT. A.21211093, Jurnal Mahasiswa S2 Hukum UNTAN (Jurnal NESTOR Magister Hukum, 2015)
AbstractThis thesis discusses the legal analysis in applying the rules of land acquisition forpublic purposes between land agency with prosecutorial republic republic IndonesiaIndonesia (study in the city singkawang).This research was conducted using themethod of normative legal research of this thesis research sosiologis.Hasil obtained:That the state land or land owned by the state, in contrast to